Climatological analysis of passage-type tropical cyclones from the Western North Pacific into the South China Sea - Jau-Ming Chen; Pei-Hua Tan; Liang Wu; Jin-Shuen Liu; Hui-Shan Chen (Terrestrial, Atmospheric and Oceanic Sciences, 2017)

(untitled)
Tropical cyclone (TC) climatological characteristics with passage from the Western North Pacific (WNP) into the South China Sea (SCS) during the June - November season are analyzed in this study. These TCs tend to form in the WNP west of 150°E, and on average westward by 7 - 12° in longitude than TCs that do not track into the SCS. Their formation locations migrate with the monsoon trough, moving northward from June to August, and southward from September to November. The probability of a WNP TC moving into the SCS varies seasonally, with only 12 - 18% of the WNP TCs doing so during August-September due to more northern TC formation. However, this probability rises to 25 - 26% in June - July and 25 - 32% in October - November with more southern TC formation. The passage-type TCs generally form in the eastern part of an elongated lower-level cyclonic anomaly of the 10-day low-pass filtered environmental circulation in the 10 - 20°N zone, which is paired with an anticyclonic anomaly to the north. Between this circulation pair, anomalous easterly flows steer these TCs westward, giving them a westward track into the SCS. The formation of these passage-type TCs is associated with a southward displacement of the monsoon trough and a westward intensification of the Pacific subtropical high in August and September. During June - July (October - November), the associated features appear as a southeastward (meridional) expansion of the monsoon trough and a northward displacement of the Pacific subtropical high.